A review of maize production and breeding in Indonesia. Issue 1 (April 2020) - Syahruddin, K; Azrai, M; Nur, A; abid, M; Wu, W Z
Abstract: Maize is one of the main commodities in Indonesia and has a significant role in maintaining the availability of other products. Maize needs in Indonesia continue to increase so that Indonesian government trying to boost maize production to substitute the need for imported maize and to achieve the target of maize self-sufficiency. To support this program, the government made a number of policies in the field of agriculture specifically for the development of maize to attract farmers to plant maize by making some policies, adapted technology and utilize unused land. The purpose of this paper is to provide an overview of the conditions of Indonesia's maize needs and how the Indonesia achieved maize self-sufficiency to substitute import maize needs also provide an overview of Indonesia maize breeding development as well. Acceleration of rate production is taken through the application of supporting technologies such as Increasing cropping index (IP), expansion of new planting areas, mechanization, superior varieties and facilities; Provision of capital, counseling and assistance; Planting maize on intercropped land with young oil palm plants, including the use of new superior varieties and cultivation technology with the Integrated Crop Management approach. The development of maize in Indonesia faces many challenges in the field by various agroecology with sub-optimal land such as saline, dry, acidic, tidal swamps, peat swamps, and shaded by plantations. To answer those challenges in maize breeding some maize varieties have been released namely Semar, Srikandi, Lamuru, Sukmaraga, variant of HJ, JH and BIMA varieties, also varieties for spesific adaptation and characteristic like JHANA (shade tolerant), JHARING (drought tolerant) and NASA-29 (prolific). In molecular breeding many markers already found to be associated to Downy Mildew Resistance (DWR) and for drougt resistance using QTL analysis and also identify patterns of spread of important maize diseases in Indonesia.